Intrauterine foetal death product as a foreign body in urinary bladder: A case report - Nahid, Md. Abu; Hasan, Mahmudul; Islam, SK Nazibul; Al Mamun, Mamun Ur Rashid; Mueed, Adnan; Islam, Md. Saiful (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Migration of intrauterine fetal death (IUD) products from the uterus to different nearby intra abdominal organ of body especially to urinary bladder is a rare clinical situation to report. Here we are presenting a case , where a woman of 54 years of age presented to us with the history of IUD at 27 weeks of gestation 17 years back with history of passage of hard brittle bony fragment like material with urine and an abdominal lump. Laparotomy was done, some parts of IUD product was found to migrate to urinary bladder cavity, some parts to incompletely invade the intestinal loops & some parts towards the abdominal wall to form the lump. Hysterectomy was done, product was removed and the entire involved organ was repaired successfully and patient cure was uneventful.